2009
DOI: 10.1016/j.molcel.2009.04.015
|View full text |Cite
|
Sign up to set email alerts
|

Polypyrimidine Tract Binding Protein Stabilizes the Encephalomyocarditis Virus IRES Structure via Binding Multiple Sites in a Unique Orientation

Abstract: Polypyrimidine tract binding (PTB) protein is a regulator of alternative pre-mRNA splicing, and also stimulates the initiation of translation dependent on many viral internal ribosome entry segments/sites (IRESs). It has four RNA-binding domains (RBDs), but although the contacts with many IRESs have been mapped, the orientation of binding (i.e., which RBD binds to which site in the IRES) is unknown. To answer this question, 16 derivatives of PTB1, each with a single cysteine flanking the RNA-binding surface in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

13
128
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 79 publications
(142 citation statements)
references
References 23 publications
13
128
1
Order By: Relevance
“…Several picornavirus IRES elements have two polypyrimidine tracts located at each end of the IRES region. In agreement with the functional role of each pyrimidine tract on IRES activity it has been found that PTB constrains the EMCV IRES structure in a unique orientation by binding to the RNA with RRM1-2 contacting the 3 end, and RRM3 contacting the 5 end of the IRES (Kafasla et al, 2009).…”
Section: Itafs Stimulating Ires Activitysupporting
confidence: 63%
“…Several picornavirus IRES elements have two polypyrimidine tracts located at each end of the IRES region. In agreement with the functional role of each pyrimidine tract on IRES activity it has been found that PTB constrains the EMCV IRES structure in a unique orientation by binding to the RNA with RRM1-2 contacting the 3 end, and RRM3 contacting the 5 end of the IRES (Kafasla et al, 2009).…”
Section: Itafs Stimulating Ires Activitysupporting
confidence: 63%
“…This parent DNTD-PTB construct, hereafter designated PTB9, also has an N-terminal His-tag, and when the two remaining cysteine residues (C250 and C251 in RBD2) were replaced by serines (Fig. 1C), it resulted in the Cys-less PTB9 construct which is used as the control in tethered hydroxyl radical probing assays of the interaction of each RBD with the target RNA, as in our previous work (Kafasla et al 2009(Kafasla et al , 2010.…”
Section: Mutants Generatedmentioning
confidence: 99%
“…To this end, the point mutations in the RNA-binding surface of a particular RBD were initially put into the background of a single cysteine derivative where the cysteine is located in the same RBD. From our library of 16 single cysteine PTB9 derivatives which all reacted efficiently with Fe(II)-BABE (Kafasla et al 2009), we selected six for these assays-one in each of RBDs2 and 3 and two in each of RBDs1 and 4 (Fig. 1C).…”
Section: Mutants Generatedmentioning
confidence: 99%
See 2 more Smart Citations